Intratumoral administration of holmium-166 acetylacetonate microspheres: antitumor efficacy and feasibility of multimodality imaging in renal cancer. - Wouter Bult; Stephanie G C Kroeze; Mattijs Elschot; Peter R Seevinck; Freek J Beekman; Hugo W A M de Jong; Donald R A Uges; Jos G W Kosterink; Peter R Luijten; Wim E Hennink; Alfred D van het Schip; J L H Ruud Bosch; et al. (PLoS ONE, 2013)
PURPOSE: The increasing incidence of small renal tumors in an aging population with comorbidities has stimulated the development of minimally invasive treatments. This study aimed to assess the efficacy and demonstrate feasibility of multimodality imaging of intratumoral administration of holmium-166 microspheres ((166)HoAcAcMS). This new technique locally ablates renal tumors through high-energy beta particles, while the gamma rays allow for nuclear imaging and the paramagnetism of holmium allows for MRI. METHODS: (166)HoAcAcMS were administered intratumorally in orthotopic renal tumors (Balb/C mice). Post administration CT, SPECT and MRI was performed. At several time points (2 h, 1, 2, 3, 7 and 14 days) after MS administration, tumors were measured and histologically analyzed. Holmium accumulation in organs was measured using inductively coupled plasma mass spectrometry. RESULTS: (166)HoAcAcMS were successfully administered to tumor bearing mice. A striking near-complete tumor-control was observed in (166)HoAcAcMS treated mice (0.10±0.01 cm(3) vs. 4.15±0.3 cm(3) for control tumors). Focal necrosis and inflammation was present from 24 h following treatment. Renal parenchyma outside the radiated region showed no histological alterations. Post administration CT, MRI and SPECT imaging revealed clear deposits of (166)HoAcAcMS in the kidney. CONCLUSIONS: Intratumorally administered (166)HoAcAcMS has great potential as a new local treatment of renal tumors for surgically unfit patients. In addition to strong cancer control, it provides powerful multimodality imaging opportunities.